Evaluating the views of paramedics, cardiologists, emergency department physicians and nurses on advanced prehospital management of acute ST elevation myocardial infarction - Rajabali, Naheed A (Pulsus Group Inc, 2009)
BACKGROUND: Although advanced prehospital management (PHM) in ST elevation myocardial infarction (STEMI) reduces reperfusion delay and improves patient outcomes, its use in North America remains uncommon. Understanding perceived barriers to and facilitators of PHM implementation may support the expansion of programs, with associated patient benefit. OBJECTIVE: To explore the attitudes and beliefs of paramedics, cardiologists, emergency physicians and nurses regarding these issues. METHODS: To maximize the potential to identify unpredictable issues within each of the four groups, focus group sessions were recorded, transcribed and analyzed for themes using the constant comparative method. RESULTS: All 18 participants believed that PHM of STEMI decreased time to treatment and improved health outcomes. Despite agreeing that most paramedics were capable of providing PHM, regular maintenance of competence and medical overview were emphasized. Significant variations in perceptions were revealed regarding practical aspects of the PHM process and protocol, as well as ownership and responsibility of the patient. Success and failures of technology were also expressed. Varying arguments against a signed ‘informed consent’ were presented by the majority. CONCLUSIONS: Focus group discussions provided key insights into potential barriers to and facilitators of PHM in STEMI. Although all groups were supportive of the concept and its benefits, concerns were expressed and potential barriers identified. This novel body of knowledge will help elucidate future educational programs and protocol development, and identify future challenges to ensure successful PHM of STEMI, thereby reducing reperfusion delay and improving patient outcomes.